DOP61 Ethnic disparities in the management of Inflammatory Bowel Disease in Israel and impact on outcomes. (30th January 2023) - Boaz, E; Ledder, O; Dagan, A; Lujan, R; Koslowsky, B; Friss, C; Greenfeld, S; Kariv, R; Loewenberg Weisband, Y; Lederman, N; Matz, E; Dotan, I; et al.
Abstract: Background: In this nationwide study, we aimed to explore health services utilization, medical management, and disease outcomes of inflammatory bowel diseases (IBD) between Jews and Arabs, the two major ethnic groups in Israel. Methods: We utilized a cohort including all patients diagnosed with IBD in Israel since 2005. The primary outcome was steroid-dependency, with secondary outcomes including use of biologics, time to surgery, and IBD-related admissions. Outcomes were controlled for possible inherent differences in disease course and phenotype. Results: Of the 32, 491 included patients, 18, 252 (56%) had Crohn's disease (CD) and 14, 239 (44%) had ulcerative colitis (UC); 10% were Arabs and 90% were Jews. Jewish ethnicity was associated with lower rates of steroid-dependency compared to Arab ethnicity in both CD )HR=0.7 [95%CI 0.6-0.8]) and UC (HR=0.7 [95%CI 0.6-0.8]). In addition, Jewish ethnicity was associated with increased use of biologics during the first year from diagnosis in patients with CD (HR=1.3 [95%CI 1.1-1.6]) but not with UC. The risk of IBD-related surgery in CD at 3 and 5 years was higher in the Arab group at all time points (13% vs 10%, 16% vs 14%, respectively, p=0.005). Arabs had higher number of IBD-related hospitalizations than Jews (19% vs. 28% with two or more IBD-related hospitalizations at 5 years, p<0.001). Conclusion: Arab ethnicity is associated with higher rate of hospitalizations, steroid-dependency and surgeries on one hand, and lower utilization of biologics on the other. The results should be considered by policy makers to improve access to medical care across all populations.